Agent assisted mobility and load aware fast handoff scheme in wireless mesh networks. (1st January 2012) - Kumar, Neeraj; Chilamkurti, Naveen
Wireless mesh networks (WMNs) have emerged as a leading technology for providing various cost effective services to the end users in recent times. In this paper, we propose a new agent assisted mobility and load aware fast handoff (AMLFH) scheme in WMNs. As mesh clients (MCs) cross different boundaries, the respective agent in that domain calculates the load on mesh gateways (MGs) and guides the incoming MCs to the suitable MGs for handoff. This mechanism reduces the handoff latency. Agents exchange the gateway load index (GLI) and handoff latency values (HLV) in their respective regions before starting the handoff procedure. The performance of the proposed AMLFH scheme is evaluated by extensive simulation using various metrics. The results obtained show that the proposed scheme is quite effective than the existing schemes with respect to the metrics defined above